Comparison of house spraying and insecticide-treated nets for malaria control - Curtis Christopher F.; Mnzava Abraham E.P (The World Health Organization, 2000)
The efficacies of using residual house spraying and insecticide-treated nets against malaria vectors are compared, using data from six recent comparisons in Africa, Asia and Melanesia. By all the entomological and malariological criteria recorded, pyrethroid-treated nets were at least as efficacious as house spraying with dichlorodiphenyltrichloroethane (DDT), malathion or a pyrethroid. However, when data from carefully monitored house spraying projects carried out between the 1950s and 1970s at Pare-Taveta and Zanzibar (United Republic of Tanzania), Kisumu (Kenya) and Garki (Nigeria) are compared with recent insecticide-treated net trials with apparently similar vector populations, the results with the insecticide-treated nets were much less impressive. Possible explanations include the longer duration of most of the earlier spraying projects and the use of non-irritant insecticides. Non-irritant insecticides may yield higher mosquito mortalities than pyrethroids, which tend to make insects leave the site of treatment (i.e. are excito-repellent). Comparative tests with non-irritant insecticides, including their use on nets, are advocated. The relative costs and sustainability of spraying and of insecticide-treated net operations are briefly reviewed for villages in endemic and epidemic situations and in camps for displaced populations. The importance of high population coverage is emphasized, and the advantages of providing treatment free of charge, rather than charging individuals, are pointed out.